The role of Banking operation in facilitating SME Financing operations in Syria (Journal of Hama University, 2019)
The study aims to identify the financing problems faced by small and medium enterprises in Syria, which hinder their growth and development, and know the role of financial institutions and the difficulties encountered in financing these projects.In order to achieve the objectives of the study, an analytical field study was conducted on the practical reality of the mechanism of the financing process, through a case study in (Syria and Overseas Bank, Syria Islamic Bank, Bank of Syria and Jordan). Using a questionnaire distributed to the employees concerned with the study of requests for funding and credit facilities and the number (95) has been retrieved (82) questionnaireThe statistical program (SPSS) was used to analyse data to arrive at the results of the study and concluded with a series of results. The most important of these are: The nature of SMEs is an obstacle to their financing by financial institutions, and the prevailing banking systems play an important role in the access of SMEs to finance.